2013
DOI: 10.1373/clinchem.2013.206359
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Picodroplet Digital PCR to Detect KRAS Mutations in Circulating DNA from the Plasma of Colorectal Cancer Patients

Abstract: This work demonstrates the clinical utility of multiplex dPCR to screen for multiple mutations simultaneously with a sensitivity sufficient to detect mutations in circulating DNA obtained by noninvasive blood collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
372
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 442 publications
(386 citation statements)
references
References 38 publications
5
372
0
9
Order By: Relevance
“…Taly et al investigated using multiplex picodroplet digital PCR (dPCR) to screen for the most common mutations in codons of the KRAS oncogene in the plasma of patients with metastatic colorectal cancer. The study showed that the higher sensitivity of this assay can screen for multiple mutations simultaneously in ctDNA (Taly et al, 2013).…”
Section: Liquid Biopsies In Tumour Diagnosis and Treatmentmentioning
confidence: 97%
“…Taly et al investigated using multiplex picodroplet digital PCR (dPCR) to screen for the most common mutations in codons of the KRAS oncogene in the plasma of patients with metastatic colorectal cancer. The study showed that the higher sensitivity of this assay can screen for multiple mutations simultaneously in ctDNA (Taly et al, 2013).…”
Section: Liquid Biopsies In Tumour Diagnosis and Treatmentmentioning
confidence: 97%
“…Il peut s'agir de cellules du microenvironnement tumoral comme de cellules saines de l'organisme [18]. Par exemple, l'ADN libre tumoral circulant peut représenter moins de 0,01 % de l'ADN libre circulant total pour des cancers à un stade précoce [14], et plus de 50 % pour des cancers métastatiques [13,19,20]. Ceci rend indispensable l'utilisation d'outils de détection plus sensibles et plus spécifiques que les techniques conventionnelles (PCR quantitative et séquençage).…”
Section: Caractéristiques De L'adn Libre Circulant Et Contraintes Liéunclassified
“…Ainsi, la dPCR est particulièremente pertinente pour la détection et la quantification de marqueurs minoritaires, incluant les sousclones rares au sein de la tumeur ou de l'ADN libre circulant. Plusieurs études récentes ont ainsi montré son intérêt pour le suivi des cancers du côlon, du poumon et du sein à partir d'échantillons de sang [20,[25][26][27].…”
Section: Caractérisation Des Altérations Génétiquesunclassified
See 1 more Smart Citation
“…Empfindliche und qualitativ hochwertige Methoden zeigen, dass cfDNA bei Tumorpatienten zu einem gegenüber anderen Diagnostikmodalitäten früheren Nachweis von Rezidiven und Entwicklungen von Therapieresistenz führt [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Die Analyse der ctDNA besitzt damit ein wichtiges Potenzial für die frühere Identifikation von Therapieversagern, wie sie zum Beispiel während der Therapie des metastasierten kolorektalen Karzinoms mit anti-EGFR Antikörpern auftreten.…”
Section: Introductionunclassified